2016
DOI: 10.1177/247553031600100206
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Psychological Comorbidities

Abstract: Psoriasis is a common systemic inflammatory disease with multiple known comorbidities. We review the literature focusing on the psychological comorbidities that have been reported. We discuss the impact of psoriasis on stress and sleep disorders in addition to depression. Alcohol abuse and nicotine addiction are prevalent in this population, as are psychological problems in children and teenagers who develop psoriasis early in life. We summarize the proposed pathophysiology and known treatments for these comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The higher prevalence of alcoholic CM in patients with psoriasis can be attributed to the higher prevalence of alcoholism in patients with psoriasis (31% vs 19%, Table 1 ). Although not statistically significant, the association between alcoholic CM and psoriasis is noticeably observed at 0.941% in our study which could be attributed to the psychosocial aspects and consequences of this debilitating autoimmune disease [ 24 , 25 ]. As viral cardiomyopathy is the only type that has been noticed to be associated with psoriasis in our current study, several explanations could justify this higher incidence.…”
Section: Discussionmentioning
confidence: 55%
“…The higher prevalence of alcoholic CM in patients with psoriasis can be attributed to the higher prevalence of alcoholism in patients with psoriasis (31% vs 19%, Table 1 ). Although not statistically significant, the association between alcoholic CM and psoriasis is noticeably observed at 0.941% in our study which could be attributed to the psychosocial aspects and consequences of this debilitating autoimmune disease [ 24 , 25 ]. As viral cardiomyopathy is the only type that has been noticed to be associated with psoriasis in our current study, several explanations could justify this higher incidence.…”
Section: Discussionmentioning
confidence: 55%
“…Focussing on the psychological impact of skin conditions has long been seen as necessary 28 if patient treatments are to be optimized, with calls growing for interventions to be more psychologically informed. 29 , 30 However, the All‐Party Parliamentary Group on Skin 31 reported that 98% of people surveyed felt psychologically negatively impacted by their skin condition, but only 18% had received support. Despite the increasing interest in psychosocial aspects of autoimmune conditions, there is a scarcity of research examining anger associated with psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriatic arthritis (PsA) is known as chronic inflammatory disease affecting skin, joints and presents high genetic polimorfism 1 . Prevalence of PsA is 2-3% population worldwide and correlates with several comorbidities 2,3 . This condition has been described as mediated by T helper cell type 17 (Th17) immune response characterized for increased levels of several proinflammatory cytokines such as interleukin (IL)-1, IL-6, IL-8, IL-17, tumor necrose factor-α (TNF-α) and a rich leukocyte recruitment mainly neutrophils into joints and skin lesions 4 .…”
Section: Introductionmentioning
confidence: 99%